Neurocognitive Performance and Depressive Symptomatology in a Group of Patients Diagnosed with Idiopathic Parkinson's Disease without Dementia. Preliminary Data from a New Scale Specifically to Assess Depression in Idiopathic Parkinson's Disease without Dementia (ESDEPARK) (2024)
To study the influence of depressive symptomatology on neurocognitive functioning in patients with Parkinson's disease (PD) in stages I and II of Hoehn and Yahr, through a scale that aims to measure depressive symptomatology specifically in PD. Depression is a neuropsychiatric pathology that appears frequently in PD, with important repercussions on the neurocognitive functioning of people with PD.